The Barbados sustainable development policy (Ministry of Housing, Lands and the Environment (Environment) St. MichaelBB, 2004)
Contains the core concepts which inform the principles of sustainable development in Barbados. Provides specific policy recommendations which will inform sustainable practices and activities in Barbados.
Additional copy located in the Office of the Secretary-General